Perancangan Komunikasi Visual Desain Website “Muggle Division” Menggunakan Kaidah UI & UX - Gilang Endra Prastowo; Dian Prajarini (AKSA: Jurnal Desain Komunikasi Visual, 2020)
"Muggle Division" is engaged in convection production services,founded 5 years ago, so far using Instagram promotion media.However, when social media cannot provide clear and completeinformation, problems arise such as when consumers are about toorder and have to wait for customer service to respond for quite along time. Therefore we need media to answer these obstacles,namely the website, to provide more complete, clear information andorder input services without having to wait for customer serviceresponses. This study aims to design a "Muggle Division" websiteequipped with a self-service order feature. The user experiencedesign method used is the five planes user experience elementsmethod followed by writing HTML, CSS, and Javascript tags. Theresult of the design is a "Muggle Division" website with UI and UXrules. The use of UI methods includes color, layout, typography,whitespace, icons, and animation. The use of the UX method is in thestep by the step payment system and page login which provides theoption of page register for visitors who are not yet a member of the"Muggle Division".